Improving Aspects of Early Childhood Cognitive Development through Play based Learning in Indonesia: A Systematic Literature Review - Salma Khoirun Nafisah; Mirawati Mirawati; Muh Asriadi AM (Aulad: Journal on Early Childhood, 2026)
Play is one of the ways in which children learn and stimulate various aspects of their development. This study aims to examine how play can enhance children’s cognitive development. The research method used was a systematic literature review following the PRISMA-P protocol, with nine journal articles serving as primary data sources. The findings indicate that structured play-based learning has a significant impact on children’s cognitive abilities, such as problem-solving, logical thinking, and symbolic thinking with educators and play materials serving as fundamental factors in optimizing developmental stimulation. For policymakers, the implications include ensuring equitable access to play resources, developing structured modules, providing professional training, and integrating play-based approaches into early childhood teacher education programs. For educators, practical recommendations include utilizing traditional games and natural materials as accessible play resources, while fostering meaningful collaboration between teachers and parents. Further research is recommended to examine the impact of free play on enhancing children’s cognitive development.